Novel α-Fe2O3/Cu-Ag-I-Cl alloy Z-scheme heterojunction for enhanced photocatalytic performance - Rajesh Kumar Thanneeru; S. Giridhar Reddy; Murtaza Bohra; Anil Annadi (Next Materials)
The generation of reactive species is crucial for several sustainable photocatalysis processes, including photodegradation, H2/O2 evolution and H2O2 synthesis. Favourable band alignment and band gap in semiconductor photocatalysts are critical for generating chemical reactive species, which often necessitate careful heterostructure design. Hematite (α-Fe2O3) nanoparticles were integrated onto Cu-Ag-I-Cl metal halide alloy with various compositions to create a new heterojunction composite. Composite formation was characterized by X-ray diffraction, UV–visible and Raman spectroscopy, as well as field emission scanning electron microscopy. X-ray photoelectron spectroscopy measurements reveal modulations in the Fe lattice, and also the traces of metallic Ag on the surface of the halide alloy. The performance of Fe2O3/Cu-Ag-I-Cl heterojunctions with different compositions as photocatalysts is assessed by photodegrading organic dyes. The composition of (Fe2O3)0.2/(Cu0.8Ag0.2I0.8Cl0.2)0.8 has shown best performance with degradation efficiency of 88 % at 100 min of UV-light exposure for Malachite green at pH 3, outperforming individual α-Fe2O3 and Cu0.8Ag0.2I0.8Cl0.2 alloy. The enhanced photocatalytic activity could be attributed to the effective separation of photogenerated carriers caused by the formation of a Z-type heterojunction and mediated by surface metallic Ag plasmonic resonance. Scavenger based trapping tests were carried out to evaluate the reactive oxygen species generation, and it was found that both hydroxyl (•OH) and superoxide (O2•−) radicals were generated and responsible for photodegradation. In light of radical generation and measured flat band potentials, a plausible photodegradation mechanism is proposed. The favourable band positions of the Fe2O3/Cu-Ag-I-Cl heterojunction emphasize its potential for sustainable applications, including H2 evolution and CO2 reduction.